2012
DOI: 10.2174/1875043501205010050
|View full text |Cite
|
Sign up to set email alerts
|

Novel Immunomodulatory Markers Expressed by Human WJ-MSC: an Updated Review in Regenerative and Reparative Medicine

Abstract: Mesenchymal (stromal) stem cells (MSC) are a broad class of stromal populations which are able to differentiate towards mature cell types, and do express molecules involved in immune modulation, tolerance induction and inflammation dampening. MSC can be virtually isolated from each adult organ, as well as from foetus-associated perinatal tissues. In particular, Wharton's jelly-derived MSC (WJ-MSC) bear all of these key properties, together with their ease of sourcing and lack of ethical issues.Cellular therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 108 publications
1
34
0
Order By: Relevance
“…T-cell anergy is mechanism by which MSCs induce immunosuppression: some authors demonstrated that the lack expression of two co-stimulatory molecules such as CD80 (B7-1) and CD86 (B7-2) by MSCs could induce an anergy state in T cells [68]. In our report, we showed by immunohistochemistry analysis that both undifferentiated and differentiated WJ-MSCs do not express the two B7 molecules.…”
Section: Discussionsupporting
confidence: 45%
“…T-cell anergy is mechanism by which MSCs induce immunosuppression: some authors demonstrated that the lack expression of two co-stimulatory molecules such as CD80 (B7-1) and CD86 (B7-2) by MSCs could induce an anergy state in T cells [68]. In our report, we showed by immunohistochemistry analysis that both undifferentiated and differentiated WJ-MSCs do not express the two B7 molecules.…”
Section: Discussionsupporting
confidence: 45%
“…As summarized by Pourrajab and co-workers, it was also supposed that the mechanisms by which BM-MSCs can reach the site of injury and exert their regulation in cardioprotection is related to the modification of extracellular matrix (ECM) under the stressed cardiac cells releasing of proteinases, such as metalloproteinases (MMPs), on the different collagen molecules [60]. MMPs constitute a broad family of extracellular proteinases which are involved in the development, function and pathogensis of several tissues and organs [62][63][64] as well as in immunomodulation by mesenchymal stem cells (reviewd in [65]). ECM fragments seem to be involved in BM-MSCs chemotaxis and were also associated to the subsequent downregulation of collagen synthesis by resident cardiac fibroblasts [60].…”
Section: Bone Marrow and Adipose-derived Mes-enchymal Stem Cellsmentioning
confidence: 99%
“…Another recent report on the use of MSCs in alleviating fibrosis showed that exosomes, released by human umbilical cord MSCs, reduced liver fibrosis, inflammation and collagen deposition in CCl4-induced fibrosis [32]. In addition, also matrix metalloproteinases, which have multiple roles in physiology and pathophysiology [33][34][35], have been suggested as key players in overcoming fibrosis effects [36].…”
Section: Physiological Liver Regeneration and Mechanisms Underlying Lmentioning
confidence: 99%
“…Several reports indicate that MSCs express non classical type I HLAs such as HLA-G (as well as its soluble form HLA-G5) [60,63,64], HLA-F and HLA-E [36]. To date, HLA-E expression has been observed in BM-MSC and WJMSCs, as well as in heart-resident MSCs [36,[65][66][67][68].…”
Section: Phenotypical Characterization and Imm-unological Features Ofmentioning
confidence: 99%
See 1 more Smart Citation